(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The influence of some mineral salts and hormonal substances on the synthesis of naphthaquinones in isolated tissues of Alkanna orientalis and Onosma sericea was studied. Exclusion of ammoniac salts from the nutrient medium as well as increasing of copper and BAP concentration intensified the synthesis of naphthaquinones in the isolated tissues of alkanet. NAA stimulated the growth of alkanet tissues, but suppressed biosynthetic processes.